Emission color management of dual emitting organic light-emitting diodes by selective switching of phosphorescence through host engineering - Jang, Ho Jin; Kim, Cho Rong; Lee, Jun Yeob (Journal of industrial and engineering chemistry (Seoul, Korea), 2021)
A device approach to manage the emission color of the organic light-emitting diodes (OLEDs) which show two emission processes of thermally activated delayed fluorescence (TADF) and phosphorescence was developed by engineering the host of the emitter. The emitting material was phenyl(10-phenyl-10H-phenoselenazin-3-yl)methanone (PSeBz) which emitted at 496 nm by TADF process and at 559 nm by phosphorescence process. The phosphorescence of the PSeBz emitter was selectively switched by the host because the triplet excitons can be intentionally quenched by the low triplet energy host. Therefore, the color coordinate of the OLEDs could be tuned from (0.35, 0.52) to (0.41, 0.52) by just changing the host of the PSeBz emitter.